A hot-dip galvanizing method and a hot-dip galvanizing steel sheet

CN122382496BActive Publication Date: 2026-09-25TIANJIN NEW SHIWANGDA NEW MATERIAL TECH CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610744208.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-05-27
Publication Date
2026-09-25
Estimated Expiration
2046-05-27

AI Technical Summary

Technical Problem

[0004]本发明的目的是提供一种热浸镀锌方法,以解决现有技术中热浸镀锌方法在极端环境下防护时间短、难以形成均匀覆盖的镀层、镀层与基体结合力不足、得到的镀件耐腐蚀性不佳的问题

Benefits of technology

(1)本发明的热浸镀锌方法,包括以下步骤:对基体依次进行酸洗、水洗、助镀处理,得到待镀基体;将待镀基体浸入第一热浸镀锌处理液中进行预镀处理,得到预镀件;将预镀件浸入第二热浸镀锌处理液中进行主镀处理,得到镀件;将镀件浸入钝化液中进行钝化处理,即可;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application provides a hot-dip galvanizing method and a hot-dip galvanizing steel plate, and the hot-dip galvanizing method comprises the following steps: sequentially performing pickling, water washing and plating-aiding treatment on a substrate to obtain a to-be-plated substrate; immersing the to-be-plated substrate into a first hot-dip galvanizing treatment solution to perform pre-plating treatment, and obtaining a pre-plated part; immersing the pre-plated part into a second hot-dip galvanizing treatment solution to perform main plating treatment, and obtaining a plated part; and immersing the plated part into a passivation solution to perform passivation treatment, and the process is completed. Through the pre-plating-main plating two-step treatment, the pre-plating is performed by immersing into a zinc solution containing aluminum elements, and the main plating is performed by immersing into a zinc solution containing aluminum elements and cerium elements, and through optimization of the components of the plating-aiding solution and the passivation solution, the uniformity, adhesion and corrosion resistance of the plated layer are enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of hot-dip galvanizing technology, and in particular to a hot-dip galvanizing method and a hot-dip galvanized steel sheet. Background Technology

[0002] Steel components are widely used in construction, transportation, machinery, power facilities, and many other fields. Corrosion and rust are common phenomena caused by the natural environment. To prevent corrosion and rust, hot-dip galvanizing is a widely adopted process for treating steel components. Hot-dip galvanizing involves immersing cleaned and activated steel workpieces in molten zinc. Through metallurgical reactions and diffusion between iron and zinc, a zinc-iron alloy layer forms on the surface, and a pure zinc layer is then applied as the outermost layer.

[0003] While existing hot-dip galvanizing processes can significantly improve the corrosion resistance of steel components, they are still insufficient in some harsh environments. When placed in humid, high-salt-spray environments, the surface will first produce white or gray corrosion products, mainly basic zinc oxide (i.e., white rust). When the zinc layer is continuously corroded until it is exhausted or penetrated, the corrosive medium will come into contact with the internal steel substrate, resulting in reddish-brown corrosion products, mainly iron oxides (i.e., red rust). This leads to the failure of the protective system, short-lasting protective effect, and frequent product replacement. In addition, the coating formed by existing hot-dip galvanizing processes on steel workpieces is prone to defects such as zinc nodules, zinc ash, runs, and incomplete coating, making it difficult to form a uniform coating. This results in insufficient adhesion between the coating and the substrate, making it easy to peel off, and thus affecting the performance of the coated parts. Summary of the Invention

[0004] The purpose of this invention is to provide a hot-dip galvanizing method to solve the problems of short protection time in extreme environments, difficulty in forming a uniform coating, insufficient adhesion between the coating and the substrate, and poor corrosion resistance of the resulting parts in the existing hot-dip galvanizing method.

[0005] This invention provides the following technical solution: A hot-dip galvanizing method includes the following steps: (1) The substrate is subjected to pickling, water washing and fluxing treatment in sequence to obtain the substrate to be plated; The fluxing solution used in the fluxing treatment includes the following raw materials: zinc chloride, ammonium chloride, potassium chloride, magnesium chloride, hexamethylenetetramine, 5-hydroxypyrazine-2-carboxylic acid, dodecyl-3-methylimidazolium chloride, and water. (2) Immerse the substrate to be plated obtained in step (1) into the first hot-dip galvanizing solution for pre-plating treatment to obtain a pre-plated part; The first hot-dip galvanizing solution contains aluminum and zinc. (3) Immerse the pre-plated part obtained in step (2) into the second hot-dip galvanizing solution for main plating treatment to obtain the plated part; The second hot-dip galvanizing solution contains aluminum, cerium, and zinc. (4) Immerse the plated part obtained in step (3) in the passivation solution for passivation treatment; The passivation solution used in the passivation treatment includes the following raw materials: nano silica, silane coupling agent, cerium nitrate, 1-(2-imidazol-1-ylethyl)piperazine, amphoteric chitosan, acetic acid, ethanol, and water.

[0006] Preferably, in step (1), the fluxing solution comprises the following raw materials in parts by weight: 90-100 parts zinc chloride, 20-30 parts ammonium chloride, 20-40 parts potassium chloride, 5-10 parts magnesium chloride, 1-5 parts hexamethylenetetramine, 1-3 parts 5-hydroxypyrazine-2-carboxylic acid, 0.5-1.5 parts dodecyl-3-methylimidazolium chloride, and 1000 parts water, with the pH value adjusted to 4.5-5.5.

[0007] Preferably, in step (2), the first hot-dip galvanizing solution comprises, by mass percentage: 0.15%-0.25% aluminum, with the remainder being zinc and unavoidable impurities.

[0008] Preferably, in step (3), the second hot-dip galvanizing solution comprises, by mass percentage: 0.15%-0.25% aluminum, 0.05%-0.20% cerium, with the remainder being zinc and unavoidable impurities.

[0009] Preferably, in step (4), the passivation solution comprises the following raw materials in parts by weight: 8-15 parts of nano-silica, 18-28 parts of silane coupling agent, 3-5 parts of cerium nitrate, 1.5-3.5 parts of 1-(2-imidazol-1-ylethyl)piperazine, 4-8 parts of amphoteric chitosan, 10-20 parts of acetic acid, 250-350 parts of ethanol, and 1000 parts of water; The silane coupling agent is at least one of aminosilane, epoxysilane, methacryloxysilane, thiosilane, and vinylsilane. The amphoteric chitosan is carboxymethyl dimethyl diallyl ammonium chloride chitosan.

[0010] Preferably, the passivation solution further includes one or more of triethanolamine borate, triisopropanolamine cycloborate, and 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt.

[0011] Preferably, the passivation solution further includes one or more of the following: 2-3 parts of triethanolamine borate, 1-2 parts of triisopropanolamine cycloborate, and 0.1-0.5 parts of 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt.

[0012] Preferably, the passivation solution further comprises 2.5 parts of triethanolamine borate, 1 part of triisopropanolamine cycloborate, and 0.3 parts of 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt.

[0013] Preferably, in step (1), the pickling includes: pickling the substrate with a 15%-20wt% hydrochloric acid solution containing 1-3g / L hexamethylenetetramine at 20-30°C for 8-12 minutes; The fluxing process includes immersing the substrate in a fluxing solution at 60-80°C for 30-120 seconds.

[0014] It should be noted that the product can be dried after the fluxing process.

[0015] Preferably, in step (2), the pre-plating includes: immersing the substrate to be plated in a first hot-dip galvanizing treatment solution at a temperature of 440-460℃ for 10-30 seconds.

[0016] Preferably, in step (3), the main plating includes immersing the pre-plated part in a second hot-dip galvanizing solution at a temperature of 460-480℃ for 60-180 seconds.

[0017] Preferably, in step (4), the passivation treatment includes immersing the plated part in a passivation solution for 1-2 minutes and drying it at 60-80°C for 10-30 minutes.

[0018] The present invention also provides a hot-dip galvanized steel sheet, comprising a substrate and a coating covering the substrate; The coating is obtained by the hot-dip galvanizing method described above; The substrate is a steel plate, and the steel plate comprises, by weight percentage: C: 0.03-0.12%, Mn: 0.08-1.8%, Si: 0.05-0.3%, Al: 0.02-0.06%, Cr: 0.1-0.4%, Mo: 0.01-0.08%, Ti: 0.01-0.06%, Nb: 0.01-0.05%, B: 0.0005-0.001%, with the balance being Fe and unavoidable impurities.

[0019] The above-described solution of the present invention has at least the following beneficial effects: (1) The hot-dip galvanizing method of the present invention includes the following steps: pickling, washing and fluxing the substrate in sequence to obtain the substrate to be galvanized; immersing the substrate to be galvanized in a first hot-dip galvanizing solution for pre-galvanizing treatment to obtain a pre-galvanized part; immersing the pre-galvanized part in a second hot-dip galvanizing solution for main galvanizing treatment to obtain a plated part; immersing the plated part in a passivation solution for passivation treatment to obtain the plated part. The hot-dip galvanizing method of the present invention uses a fluxing solution comprising zinc chloride, ammonium chloride, potassium chloride, magnesium chloride, hexamethylenetetramine, 5-hydroxypyrazine-2-carboxylic acid, dodecyl-3-methylimidazolium chloride, and water. Zinc chloride is the main salt for forming the salt film; ammonium chloride is an activator that removes the oxide film on the substrate surface and ensures wetting; potassium chloride and magnesium chloride improve the wetting effect; hexamethylenetetramine (also known as hexamethylenetetramine) acts as a corrosion inhibitor; and dodecyl-3-methylimidazolium chloride is an ionic liquid that reduces the surface tension of the fluxing solution, increases the wetting speed and coverage uniformity. More importantly, its imidazole rings can be adsorbed onto the surface of the substrate, and the long alkyl chains provide steric hindrance. During fluxing, it works synergistically with hexamethylenetetramine to inhibit corrosion. During pre-plating and main plating, it affects the interdiffusion of iron and zinc atoms, inhibits the excessive growth of the brittle phase (Γ phase, ζ phase) in the iron-zinc reaction, and promotes the stable growth of the tough phase (δ phase). The 5-hydroxypyrazine-2-carboxylic acid contains a pyrazine ring, hydroxyl group, and carboxyl group. Compared with the dodecyl-3-methylimidazolium chloride, it has stronger polarity and can selectively adsorb onto the highly active sites of the matrix. It can regulate the diffusion rate of iron and zinc atoms and the local reaction rate at the grain boundaries, inhibit dendrite growth, eliminate zinc nodules, and cooperate with the dodecyl-3-methylimidazolium chloride to obtain a more uniform coating with better adhesion.

[0020] This invention employs a two-step pre-plating and main plating process. First, the plating is performed by immersing the plating in a zinc bath containing aluminum to form a continuous Fe-Zn-Al alloy layer. This layer has strong adhesion to the substrate, providing a solid base for the entire plating system and inhibiting excessive iron-zinc reaction. Then, the plating is performed by immersing the plating in a zinc bath containing aluminum and cerium to form a Zn-Al-Ce alloy layer. This refines the zinc alloy plating grains, making the plating denser, more uniform, and defect-free, thus enhancing its corrosion resistance.

[0021] The hot-dip galvanizing method of this invention uses a passivation solution comprising: nano-silica, a silane coupling agent, cerium nitrate, 1-(2-imidazol-1-ylethyl)piperazine, amphoteric chitosan, acetic acid, ethanol, and water. The nano-silica forms an inorganic barrier layer on the coating surface, filling the micropores of the coating, improving the density and wear resistance of the passivation film, and enhancing the physical shielding effect against corrosive media. The silane coupling agent, after hydrolysis, forms Si-OH, which condenses with Zn-OH on the zinc layer surface to form Si-O-Zn covalent bonds, and self-polymerizes to form a Si-O-Si three-dimensional network, constituting the film framework and improving the adhesion of the passivation film. The cerium nitrate, together with cerium in the main plating layer, synergistically enhances corrosion resistance. The amphoteric chitosan complexes with cerium ions, anchoring the corrosion inhibitor in the passivation film, and forms an organic-inorganic hybrid network with the silane coupling agent, forming a highly adhesive biopolymer film that improves the ability to block corrosive media. The 1-(2-imidazol-1-ylethyl)piperazine, as a bi-heterocyclic film-forming aid, allows imidazolium to form complexes with cerium and zinc ions. Compared to the flexible coordination of the macromolecular sites of the amphoteric chitosan, its site binding is faster, serving as a nucleation center. Working together with the amphoteric chitosan, it makes the passivation film growth more uniform and improves the film density. The introduction of the piperazine ring can refine the grains, reduce passivation film defects, and further enhance the ability to shield against corrosive media. The ethyl group serves as the connecting arm between imidazolium and the piperazine ring, making it relatively stable and flexible, ensuring that imidazolium and the piperazine ring can fully exert their effects.

[0022] (2) In the hot-dip galvanizing method of the present invention, the amphoteric chitosan is carboxymethyl dimethyl diallyl ammonium chloride chitosan. Carboxymethyl and dimethyl diallyl ammonium chloride are introduced into the molecular chain of chitosan at the same time, which not only improves the solubility of chitosan in the passivation solution, but also makes its molecular chain spatial conformation more extended. When the hydroxyl and carboxyl groups on its molecular chain are combined with silane coupling agents, cerium ions, etc., more flexible network bridging can be achieved, thereby effectively filling and bridging the microscopic defects in the inorganic network. Detailed Implementation

[0023] Unless otherwise specified in the embodiments of this invention, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all commercially available products; different manufacturers and models of raw materials do not affect the implementation of the technical solution or the achievement of the technical effect of this invention.

[0024] The CAS number of the 5-hydroxypyrazine-2-carboxylic acid is 34604-60-9; the CAS number of the dodecyl-3-methylimidazolium chloride is 114569-84-5; the CAS number of the 1-(2-imidazol-1-ylethyl)piperazine is 381721-55-7; the amphoteric chitosan is a known product in the prior art, and its specific carboxymethyl dimethyl diallyl ammonium chloride chitosan can be prepared by existing technology, for example, by grafting dimethyl diallyl ammonium chloride (DMDAAC) onto the carboxymethyl chitosan backbone. The silane coupling agents mentioned are all existing technology products. For example, aminosilane can be γ-aminopropyltriethoxysilane (KH-550); epoxysilane can be 3-glycidyl etheroxypropyltrimethoxysilane (KH-560); methacryloxysilane can be 3-methacryloxypropyltrimethoxysilane (KH-570); thiosilane can be 3-mercaptopropyltrimethoxysilane (KH-590); and vinylsilane can be vinyltriethoxysilane (KH-151). The CAS number of the hydroxypyrazine is 6270-63-9. The CAS number of the sodium dodecyl sulfonate is 2386-53-0.

[0025] Example 1 The hot-dip galvanizing method of this embodiment includes the following steps: (1) The substrate is subjected to pickling, water washing and fluxing treatment in sequence to obtain the substrate to be plated; The pickling process includes pickling the substrate in a 20wt% hydrochloric acid solution containing 1g / L hexamethylenetetramine at 30°C for 8 minutes. The water washing includes: using water washing to remove the pickling solution adhering to the outer surface of the substrate and some of the metal salts generated during the pickling process; the water washing is implemented using existing technology, and those skilled in the art can select appropriate process conditions such as water washing time according to the actual situation (the same applies below, and will not be repeated hereafter).

[0026] The fluxing treatment includes: immersing the substrate in a fluxing solution at 80°C for 30 seconds, and then drying it; the fluxing solution includes the following raw materials in parts by weight: 100 parts zinc chloride, 30 parts ammonium chloride, 20 parts potassium chloride, 5 parts magnesium chloride, 3 parts hexamethylenetetramine, 2 parts 5-hydroxypyrazine-2-carboxylic acid, 1.0 part dodecyl-3-methylimidazolium chloride, and 1000 parts water, adjusting the pH value to 5.5.

[0027] (2) Immerse the substrate to be plated obtained in step (1) into the first hot-dip galvanizing treatment solution at a temperature of 460°C and pre-plate for 20 seconds to obtain the pre-plated part; the first hot-dip galvanizing treatment solution includes 0.19% aluminum by mass percentage, and the remainder is zinc and unavoidable impurities.

[0028] (3) Immerse the pre-plated part obtained in step (2) into the second hot-dip galvanizing treatment solution at a temperature of 480°C and perform the main plating for 60 seconds to obtain the plated part; the second hot-dip galvanizing treatment solution includes, by mass percentage: 0.25% aluminum element, 0.10% cerium element, and the remainder is zinc element and unavoidable impurities.

[0029] (4) Immerse the plated part obtained in step (3) in the passivation solution for 2 minutes and dry it at 60°C for 15 minutes. The passivation solution comprises the following raw materials in parts by weight: 8 parts nano-silica, 25 parts silane coupling agent, 3 parts cerium nitrate, 3.5 parts 1-(2-imidazol-1-ylethyl)piperazine, 4 parts amphoteric chitosan, 10 parts acetic acid, 350 parts ethanol, and 1000 parts water; the silane coupling agent is methacryloxysilane; and the amphoteric chitosan is carboxymethyl dimethyl diallyl ammonium chloride chitosan.

[0030] It should be noted that in this embodiment, the substrate is a steel product, including but not limited to steel components, steel plates, steel profiles, and various steel parts. In this embodiment, the substrate is a 5mm thick steel plate, which, by weight percentage, comprises: C: 0.08%, Mn: 1.2%, Si: 0.15%, Al: 0.04%, Cr: 0.2%, Mo: 0.05%, Ti: 0.03%, Nb: 0.03%, B: 0.0008%, with the balance being Fe and unavoidable impurities. Hot-dip galvanized steel sheets can be obtained through the hot-dip galvanizing method of this embodiment (the same applies below, and will not be repeated later).

[0031] Example 2 The hot-dip galvanizing method of this embodiment includes the following steps: (1) The substrate is subjected to pickling, water washing and fluxing treatment in sequence to obtain the substrate to be plated; The pickling process includes pickling the substrate in a 17wt% hydrochloric acid solution containing 3g / L hexamethylenetetramine at 20°C for 12min. The water washing includes: using water washing to remove the pickling solution adhering to the outer surface of the substrate and some of the metal salts generated during the pickling process; The fluxing treatment includes: immersing the substrate in a fluxing solution at 60°C for 60 seconds, and then drying it; the fluxing solution includes the following raw materials in parts by weight: 90 parts zinc chloride, 25 parts ammonium chloride, 40 parts potassium chloride, 8 parts magnesium chloride, 1 part hexamethylenetetramine, 1 part 5-hydroxypyrazine-2-carboxylic acid, 0.5 parts dodecyl-3-methylimidazolium chloride, and 1000 parts water, adjusting the pH value to 5.0.

[0032] (2) Immerse the substrate to be plated obtained in step (1) into the first hot-dip galvanizing treatment solution at a temperature of 440°C and pre-plate for 30 seconds to obtain the pre-plated part; the first hot-dip galvanizing treatment solution includes 0.15% aluminum by mass percentage, and the remainder is zinc and unavoidable impurities.

[0033] (3) Immerse the pre-plated part obtained in step (2) into the second hot-dip galvanizing treatment solution at a temperature of 470°C and perform the main plating for 120 seconds to obtain the plated part; the second hot-dip galvanizing treatment solution includes, by mass percentage: 0.15% aluminum element, 0.20% cerium element, and the remainder is zinc element and unavoidable impurities.

[0034] (4) Immerse the plated part obtained in step (3) in the passivation solution for 1 minute and dry it at 80°C for 10 minutes. The passivation solution comprises the following raw materials in parts by weight: 15 parts nano-silica, 28 parts silane coupling agent, 5 parts cerium nitrate, 2.5 parts 1-(2-imidazol-1-ylethyl)piperazine, 8 parts amphoteric chitosan, 15 parts acetic acid, 250 parts ethanol, and 1000 parts water; the silane coupling agent is a mixture of thiosilane and vinylsilane in a 1:1 ratio; the amphoteric chitosan is carboxymethyl dimethyl diallyl ammonium chloride chitosan.

[0035] Example 3 The hot-dip galvanizing method of this embodiment includes the following steps: (1) The substrate is subjected to pickling, water washing and fluxing treatment in sequence to obtain the substrate to be plated; The pickling process includes pickling the substrate in a 15wt% hydrochloric acid solution containing 2g / L hexamethylenetetramine at 30°C for 10min. The water washing includes: using water washing to remove the pickling solution adhering to the outer surface of the substrate and some of the metal salts generated during the pickling process; The fluxing treatment includes: immersing the substrate in a fluxing solution at 70°C for 120 seconds, and then drying it; the fluxing solution comprises the following raw materials in parts by weight: 95 parts zinc chloride, 20 parts ammonium chloride, 30 parts potassium chloride, 10 parts magnesium chloride, 5 parts hexamethylenetetramine, 3 parts 5-hydroxypyrazine-2-carboxylic acid, 1.5 parts dodecyl-3-methylimidazolium chloride, and 1000 parts water, adjusting the pH value to 4.5.

[0036] (2) Immerse the substrate to be plated obtained in step (1) into the first hot-dip galvanizing treatment solution at a temperature of 445°C and pre-plate for 10 seconds to obtain the pre-plated part; the first hot-dip galvanizing treatment solution includes 0.25% aluminum by mass percentage, and the remainder is zinc and unavoidable impurities.

[0037] (3) Immerse the pre-plated part obtained in step (2) into the second hot-dip galvanizing treatment solution at a temperature of 460°C and perform the main plating for 180 seconds to obtain the plated part; the second hot-dip galvanizing treatment solution includes, by mass percentage: 0.20% aluminum element, 0.05% cerium element, and the remainder is zinc element and unavoidable impurities.

[0038] (4) Immerse the plated part obtained in step (3) in the passivation solution for 1.5 min and dry it at 70°C for 30 min. The passivation solution comprises the following raw materials in parts by weight: 12 parts nano-silica, 18 parts silane coupling agent, 4 parts cerium nitrate, 1.5 parts 1-(2-imidazol-1-ylethyl)piperazine, 7 parts amphoteric chitosan, 20 parts acetic acid, 300 parts ethanol, and 1000 parts water; the silane coupling agent is a mixture of aminosilane and epoxysilane in a 1:1 ratio; the amphoteric chitosan is carboxymethyl dimethyl diallyl ammonium chloride chitosan.

[0039] Example 4 The hot-dip galvanizing method of this embodiment includes the following steps: (1) The substrate is subjected to pickling, water washing and fluxing treatment in sequence to obtain the substrate to be plated; The pickling process includes pickling the substrate in a 18wt% hydrochloric acid solution containing 2g / L hexamethylenetetramine at 25°C for 10min. The water washing includes: using water washing to remove the pickling solution adhering to the outer surface of the substrate and some of the metal salts generated during the pickling process; The fluxing treatment includes: immersing the substrate in a fluxing solution at 75°C for 60 seconds, and then drying it; the fluxing solution includes the following raw materials in parts by weight: 95 parts zinc chloride, 25 parts ammonium chloride, 30 parts potassium chloride, 8 parts magnesium chloride, 3 parts hexamethylenetetramine, 2 parts 5-hydroxypyrazine-2-carboxylic acid, 1.0 part dodecyl-3-methylimidazolium chloride, and 1000 parts water, adjusting the pH value to 5.0.

[0040] (2) Immerse the substrate to be plated obtained in step (1) into the first hot-dip galvanizing treatment solution at a temperature of 450°C and pre-plate for 20 seconds to obtain the pre-plated part; the first hot-dip galvanizing treatment solution includes 0.20% aluminum by mass percentage, and the remainder is zinc and unavoidable impurities.

[0041] (3) Immerse the pre-plated part obtained in step (2) into the second hot-dip galvanizing treatment solution at a temperature of 470°C and perform the main plating for 120 seconds to obtain the plated part; the second hot-dip galvanizing treatment solution includes, by mass percentage: 0.20% aluminum element, 0.12% cerium element, and the remainder is zinc element and unavoidable impurities.

[0042] (4) Immerse the plated part obtained in step (3) in the passivation solution for 1.5 min and dry it at 70°C for 20 min. The passivation solution comprises the following raw materials in parts by weight: 12 parts nano-silica, 23 parts silane coupling agent, 4 parts cerium nitrate, 2.5 parts 1-(2-imidazol-1-ylethyl)piperazine, 6 parts amphoteric chitosan, 15 parts acetic acid, 300 parts ethanol, and 1000 parts water; the silane coupling agent is a mixture of aminosilane and epoxysilane in a 1:1 ratio; the amphoteric chitosan is carboxymethyl dimethyl diallyl ammonium chloride chitosan.

[0043] Example 5 The hot-dip galvanizing method in this embodiment is basically the same as that in Example 4, except that in step (3), the passivation solution also includes 2.5 parts of triethanolamine borate, 1 part of triisopropanolamine cycloborate, and 0.3 parts of 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt.

[0044] Example 6 The hot-dip galvanizing method in this embodiment is basically the same as that in embodiment 4, except that in step (3), the passivation solution also includes 2.5 parts of triethanolamine borate and 1 part of triisopropanolamine cycloborate.

[0045] Example 7 The hot-dip galvanizing method in this embodiment is basically the same as that in embodiment 4, except that in step (4), the passivation solution also includes 2.5 parts of triethanolamine borate.

[0046] Example 8 The hot-dip galvanizing method in this embodiment is basically the same as that in embodiment 4, except that in step (4), the passivation solution also includes 1 part of triisopropanolamine cycloborate.

[0047] Example 9 The hot-dip galvanizing method in this embodiment is basically the same as that in embodiment 4, except that in step (4), the passivation solution also includes 0.5 parts of 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt.

[0048] Example 10 The hot-dip galvanizing method in this embodiment is basically the same as that in embodiment 4, except that in step (4), the passivation solution also includes 2.5 parts of triethanolamine borate and 0.3 parts of 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt.

[0049] Example 11 The hot-dip galvanizing method in this embodiment is basically the same as that in embodiment 4, except that in step (4), the passivation solution also includes 1 part of triisopropanolamine cycloboronic acid ester and 0.3 parts of 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt.

[0050] Comparative Example 1 The hot-dip galvanizing method of this comparative example is basically the same as that of Example 4, except that in step (1), the 5-hydroxypyrazine-2-carboxylic acid in the flux is replaced with hydroxypyrazine.

[0051] Comparative Example 2 The hot-dip galvanizing method of this comparative example is basically the same as that of Example 4, except that in step (1), the 5-hydroxypyrazine-2-carboxylic acid in the flux is replaced with pyrazine.

[0052] Comparative Example 3 The hot-dip galvanizing method of this comparative example is basically the same as that of Example 4, except that in step (1), the dodecyl-3-methylimidazolium chloride in the flux is replaced with sodium dodecyl sulfonate.

[0053] Comparative Example 4 The hot-dip galvanizing method of this comparative example is basically the same as that of Example 4, except that in step (1), the flux does not contain 5-hydroxypyrazine-2-carboxylic acid and dodecyl-3-methylimidazolium chloride.

[0054] Comparative Example 5 The hot-dip galvanizing method of this comparative example is basically the same as that of Example 4, except that in step (1), the flux does not contain 5-hydroxypyrazine-2-carboxylic acid.

[0055] Comparative Example 6 The hot-dip galvanizing method of this comparative example is basically the same as that of Example 4, except that in step (1), the flux does not contain dodecyl-3-methylimidazolium chloride.

[0056] Comparative Example 7 The hot-dip galvanizing method of this comparative example is basically the same as that of Example 4, except that steps (2) and (3) are combined into one step, that is, the substrate to be galvanized is directly immersed in the first hot-dip galvanizing treatment solution at a temperature of 450°C for 140 seconds.

[0057] Comparative Example 8 The hot-dip galvanizing method of this comparative example is basically the same as that of Example 4, except that steps (2) and (3) are combined into one step, that is, the substrate to be galvanized is directly immersed in the second hot-dip galvanizing treatment solution at a temperature of 470°C for 140 seconds.

[0058] Comparative Example 9 The hot-dip galvanizing method of this comparative example is basically the same as that of Example 4, except that the passivation solution in step (4) does not contain 1-(2-imidazol-1-ylethyl)piperazine.

[0059] Comparative Example 10 The hot-dip galvanizing method of this comparative example is basically the same as that of Example 4, except that in step (4), the amphoteric chitosan in the passivation solution is replaced with unmodified chitosan.

[0060] Comparative Example 11 The hot-dip galvanizing method of this comparative example is basically the same as that of Example 4, except that in step (4), 1-(2-imidazol-1-ylethyl)piperazine in the passivation solution is replaced with N-ethylpiperazine.

[0061] Comparative Example 12 The hot-dip galvanizing method of this comparative example is basically the same as that of Example 4, except that the passivation solution in step (4) does not contain amphoteric chitosan.

[0062] Effect Experiment Example To verify the technical effect of the hot-dip galvanizing method described in this invention, the products prepared in Examples 1-11 and Comparative Examples 1-12 were subjected to the following tests: (1) Coating thickness and uniformity test The sample was analyzed using a scanning electron microscope. The coating thickness was measured in five fields of view, and the arithmetic mean of the measured values ​​was taken as the coating thickness. The maximum and minimum coating thickness were measured in each field of view, and then the average of the maximum and minimum values ​​was taken. The coating thickness deviation was represented by the difference between the average of the maximum and minimum values.

[0063] (2) Adhesion test The sample was subjected to repeated bending tests until it broke at the point of repeated bending. The zinc coating was observed to peel or fall off at the fracture surface. The adhesion grade of the hot-dip galvanized coating was evaluated according to the following method.

[0064] Grade 0: No peeling or flaking; Grade 1: Localized peeling, but not detached, with no visible substrate; Level 2: Localized detachment, small pieces falling off, the substrate is visible; Level 3: Large-area peeling, with large areas of exposed substrate.

[0065] (3) Coating corrosion resistance test Salt spray corrosion chamber was used to conduct salt spray tests on the samples under the following conditions: 5±1% NaCl solution, pH 6.5-7.2, continuous spraying at 35±2℃, no drying cycle, sample tilt angle of 15°-30°, and inspection every 24 hours. When the red rust area was ≥1%, the time of red rust appearance was recorded.

[0066] (4) Cyclic acceleration test The cyclic accelerated testing of the samples was carried out in accordance with GB / T 20854-2025, and the specific test conditions are as follows: Salt spray conditions: 5±1% NaCl solution, pH 6.5-7.2, spraying at 35±2℃; "Dry" conditions: air drying, temperature 60±2℃, relative humidity <30%RH; “Wet” conditions: Ensure no condensation occurs on the sample, temperature 50±1℃, relative humidity >90%RH; Single cycle: Total time 8 hours, including 2 hours of salt spray, 4 hours of "dry" spray, and 2 hours of "wet" spray; Sample tilt angle: 20±5°; Observation period: Observations were conducted at 168h (7 days), 504h (21 days), and 1008h (42 days), and the area of ​​red rust was recorded.

[0067] The test results of Examples 1-11 and Comparative Examples 1-12 are shown in Table 1.

[0068] Table 1 Test Results Based on the above results, it can be seen that the hot-dip galvanized material obtained by the present invention exhibits excellent performance in terms of coating uniformity, adhesion, and corrosion resistance. Specifically, the hot-dip galvanized layers prepared in Examples 1-11 have uniform thickness with deviations all below 5 μm; the coating adhesion is good, all at grade 0; in the corrosion resistance test, the time for red rust to appear is greater than 38 days; in the accelerated cycling test, the proportion of red rust area is less than 10% after 1008 hours; this indicates that the hot-dip galvanizing method of the present invention can effectively improve the uniformity, adhesion, and corrosion resistance of the coating.

[0069] Based on the results of Example 4 and Comparative Examples 1-6, it is evident that the flux significantly affects the uniformity, adhesion, and corrosion resistance of the coating. The flux containing 5-hydroxypyrazine-2-carboxylic acid and dodecyl-3-methylimidazolium chloride resulted in coatings with excellent uniformity, adhesion, and corrosion resistance. Comparative Example 4, lacking both 5-hydroxypyrazine-2-carboxylic acid and dodecyl-3-methylimidazolium chloride, exhibited a significantly increased thickness deviation in the hot-dip galvanized coating, and a marked decrease in coating adhesion and corrosion resistance. Compared to Example 4, Comparative Examples 1 and 2, although containing pyrazine ring structures, showed significantly superior overall performance due to the presence of 5-hydroxypyrazine-2-carboxylic acid. Comparative Example 6 lacked dodecyl-3-methylimidazolium chloride, while Comparative Example 3, by replacing dodecyl-3-methylimidazolium chloride with sodium dodecyl sulfonate, showed a significant performance improvement, but the overall performance remained unsatisfactory. In addition, compared with changes in the composition of the passivation solution and the process design of pre-plating followed by main plating, the composition of the flux has the greatest impact on the results of the accelerated cyclic test. This is because the accelerated cyclic test involves not only salt corrosion but also alternating wet and dry conditions and stress cycles, which amplifies the integrity of the coating, interfacial bonding, and defects, thus evaluating the overall performance of the coating.

[0070] According to the results of Example 4 and Comparative Examples 7-8, the hot-dip galvanized coating obtained by the two-step method of pre-plating + main plating of the present invention has better coating uniformity and adhesion, and its corrosion resistance in the accelerated cyclic test is significantly improved.

[0071] Based on the results of Example 4 and Comparative Examples 9-12, it can be seen that Example 4, which contains 1-(2-imidazol-1-ylethyl)piperazine and amphoteric chitosan in its passivation solution, exhibits superior corrosion resistance. Comparative Example 9, which does not contain 1-(2-imidazol-1-ylethyl)piperazine, and Comparative Example 12, which does not contain amphoteric chitosan, show significantly reduced coating uniformity and corrosion resistance. In Comparative Example 10, replacing the amphoteric chitosan with unmodified chitosan in the passivation solution significantly reduces the coating's corrosion resistance. In Comparative Example 11, replacing 1-(2-imidazol-1-ylethyl)piperazine with N-ethylpiperazine in the passivation solution results in corrosion resistance similar to that of Comparative Example 9.

[0072] Based on the results of Examples 4 and 5-11, it can be seen that Examples 7-9, which contain triethanolamine borate, triisopropanolamine cycloborate, and 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt in the passivation solution, have little impact on the coating thickness uniformity and adhesion, but improve corrosion resistance in the accelerated cycling test. Examples 10 and 11, which use a combination of triethanolamine borate and 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt in the passivation solution, show a more significant improvement in corrosion resistance. However, Example 5, which simultaneously contains triethanolamine borate, triisopropanolamine cycloborate, and 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt, shows a significant improvement in corrosion resistance. Triethanolamine borate primarily functions as a corrosion inhibitor and film-forming promoter, forming an adsorption layer on the metal surface and participating in the construction of the passivation film, thus enhancing its adhesion. Triisopropanolamine cycloborate, on the other hand, possesses larger hydrophobic groups, providing corrosion inhibition while adjusting the hydrophobicity and density of the passivation film, thereby enhancing its salt spray resistance. When both are used in combination with 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt, a significant synergistic effect can be achieved.

[0073] As is known from common technical knowledge, this invention can be implemented through other embodiments that do not depart from its spirit or essential characteristics. Therefore, the disclosed embodiments described above are merely illustrative in all respects and are not the only ones. All modifications within the scope of this invention or equivalent to the scope of this invention should be considered to fall within the protection scope of this invention.

Claims

1. A hot-dip galvanizing method, characterized in that, Includes the following steps: (1) The substrate is subjected to pickling, water washing and fluxing treatment in sequence to obtain the substrate to be plated; The fluxing solution used in the fluxing treatment comprises the following raw materials in parts by weight: 90-100 parts zinc chloride, 20-30 parts ammonium chloride, 20-40 parts potassium chloride, 5-10 parts magnesium chloride, 1-5 parts hexamethylenetetramine, 1-3 parts 5-hydroxypyrazine-2-carboxylic acid, 0.5-1.5 parts dodecyl-3-methylimidazolium chloride, and 1000 parts water, with the pH adjusted to 4.5-5.

5. (2) Immerse the substrate to be plated obtained in step (1) into the first hot-dip galvanizing solution for pre-plating treatment to obtain a pre-plated part; The first hot-dip galvanizing solution comprises, by mass percentage: 0.15%-0.25% aluminum, with the remainder being zinc and unavoidable impurities; (3) Immerse the pre-plated part obtained in step (2) into the second hot-dip galvanizing solution for main plating treatment to obtain the plated part; The second hot-dip galvanizing solution comprises, by mass percentage: 0.15%-0.25% aluminum, 0.05%-0.20% cerium, with the remainder being zinc and unavoidable impurities; (4) Immerse the plated part obtained in step (3) in the passivation solution for passivation treatment; The passivation solution used in the passivation treatment comprises the following raw materials in parts by weight: 8-15 parts of nano-silica, 18-28 parts of silane coupling agent, 3-5 parts of cerium nitrate, 1.5-3.5 parts of 1-(2-imidazol-1-ylethyl)piperazine, 4-8 parts of amphoteric chitosan, 10-20 parts of acetic acid, 250-350 parts of ethanol, and 1000 parts of water; The silane coupling agent is at least one of aminosilane, epoxysilane, methacryloxysilane, thiosilane, and vinylsilane. The amphoteric chitosan is carboxymethyl dimethyl diallyl ammonium chloride chitosan.

2. The hot-dip galvanizing method according to claim 1, characterized in that, In step (1), the pickling includes: pickling the substrate with a 15%-20wt% hydrochloric acid solution containing 1-3g / L hexamethylenetetramine at 20-30℃ for 8-12min; The fluxing process includes immersing the substrate in a fluxing solution at 60-80°C for 30-120 seconds.

3. The hot-dip galvanizing method according to claim 1, characterized in that, In step (2), the pre-plating includes immersing the substrate to be plated in a first hot-dip galvanizing solution at a temperature of 440-460℃ for 10-30 seconds.

4. The hot-dip galvanizing method according to claim 1, characterized in that, In step (3), the main plating includes immersing the pre-plated part in a second hot-dip galvanizing solution at a temperature of 460-480℃ for 60-180 seconds.

5. The hot-dip galvanizing method according to claim 1, characterized in that, In step (4), the passivation treatment includes immersing the plated part in the passivation solution for 1-2 minutes and drying it at 60-80°C for 10-30 minutes.

6. A hot-dip galvanized steel sheet, characterized in that, It includes a substrate and a coating covering the substrate; obtained by the hot-dip galvanizing method according to any one of claims 1-5; The substrate is a steel plate.

7. The hot-dip galvanized steel sheet according to claim 6, characterized in that, The steel plate comprises, by weight percentage: C: 0.03-0.12%, Mn: 0.08-1.8%, Si: 0.05-0.3%, Al: 0.02-0.06%, Cr: 0.1-0.4%, Mo: 0.01-0.08%, Ti: 0.01-0.06%, Nb: 0.01-0.05%, B: 0.0005-0.001%, with the balance being Fe and unavoidable impurities.

Citation Information

Patent Citations

  • Hot-dip galvanizing method for steel

    CN113699475A

  • Hot-dip galvanizing process for metal plating piece

    CN114807812A